PENGARUH VARIASI KONSENTRASI HPMC TERHADAP MUTU FISIK DAN STABILITAS SEDIAAN SHAMPO EKSTRAK ETANOL DAUN KATUK (Sauropus androgynus (L) Merr) - Dewi Rashati, Mikhania Christiningtyas Eryani (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2016)
The Aims of this study was to determine effect of HPMC concentration variation to etanol extract Sauropus androgynus (L) Merr shampoo physical properties. True experimental laboratories design was used as design study. Shampoo was formulated in three formulation which used HPMC variation consentration were F1 (1%), F2 (2%) , F3 (3%). Shampoo was evaluated physical properties included organoleptic, pH, viscosity, foam forming, and stability test at 6oC, 300C and 40oC. Organoleptic test was observed by visual observation. pH, viscosity, foam forming, and stability test from three formulation were observed by one way anova statistic. The result showed that HPMC concentration variation didn’t influence to physical properties foam forming and pH shampoo but there had influence to physical properties viscosity. All formulation of formulation unstable during 6 weeks storage.Keywords: Shampoo, etanol extract Sauropus androgynus (L) Merr, HPMC